Classroom - Mishra S.; Namdev A.; Bisen M.; Ahmad J.; Mishra V. (My University, 2025)
In this section of Resonance, we invite readers to pose questions likely to be raised in a classroom situation. We may suggest strategies for dealing with them, or invite responses, or both. “Classroom” is equally a forum for raising broader issues and sharing personal experiences and viewpoints on matters related to teaching and learning science. © 2016, Indian Academy of Sciences.